(untitled) (Kindle, 2025)
Clinical decision-making using artificial intelligence represents a significant evolution in modern healthcare. Traditionally, clinical decisions have relied on physician experience, clinical guidelines, and manual interpretation of diagnostic data. As medical data have grown in volume and complexity, artificial intelligence has emerged as a valuable tool to support clinicians in synthesizing information and reducing uncertainty. Artificial intelligence systems analyze large and diverse datasets, including electronic health records, medical imaging, laboratory results, physiologic signals, and clinical text. Through machine learning and deep learning techniques, these systems identify patterns that may not be easily recognized by humans. This capability supports earlier diagnosis, more accurate risk stratification, and personalized treatment planning. In time sensitive settings, artificial intelligence can assist in prioritizing patients, predicting deterioration, and supporting rapid interventions. Importantly, artificial intelligence functions as a clinical decision support tool rather than a replacement for clinician judgment. Human oversight remains essential to interpret outputs, account for patient preferences, and manage ethical considerations. Well designed artificial intelligence systems are integrated into clinical workflows, providing recommendations that are transparent, interpretable, and actionable. Despite its promise, the use of artificial intelligence in clinical decision-making presents challenges. These include data quality, algorithmic bias, generalizability across populations, and concerns about privacy and accountability. Addressing these issues requires rigorous validation, ongoing monitoring, and clear governance frameworks. When implemented responsibly, artificial intelligence enhances clinical decision-making by improving consistency, efficiency, and precision. Its thoughtful integration has the potential to support clinicians, improve patient outcomes, and contribute to a more adaptive and data driven healthcare system.